2016
DOI: 10.1371/journal.pone.0164161
|View full text |Cite
|
Sign up to set email alerts
|

Single and Serial Fetal Biometry to Detect Preterm and Term Small- and Large-for-Gestational-Age Neonates: A Longitudinal Cohort Study

Abstract: ObjectivesTo assess the value of single and serial fetal biometry for the prediction of small- (SGA) and large-for-gestational-age (LGA) neonates delivered preterm or at term.MethodsA cohort study of 3,971 women with singleton pregnancies was conducted from the first trimester until delivery with 3,440 pregnancies (17,334 scans) meeting the following inclusion criteria: 1) delivery of a live neonate after 33 gestational weeks and 2) two or more ultrasound examinations with fetal biometry parameters obtained at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 43 publications
3
41
1
1
Order By: Relevance
“…There are few reports about longitudinal (or serial) growth assessment for the prediction of LGA and macrosomia in unselected pregnancies, with conflicting results [10][11][12]. Hedriana and Moore [10] used averaged centiles from several ultrasound assessments between 28 and 42 weeks in 263 normal singleton pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few reports about longitudinal (or serial) growth assessment for the prediction of LGA and macrosomia in unselected pregnancies, with conflicting results [10][11][12]. Hedriana and Moore [10] used averaged centiles from several ultrasound assessments between 28 and 42 weeks in 263 normal singleton pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Salomon et al [11] assessed 356 normal singleton pregnancies for fetal growth potential (based on fetal biometry, fetal growth velocity [averaged z scores], and gestational age) and found that it can improve identification of fetuses at risk for late-onset growth abnormalities. A recent report by Tarca et al [12], in a large cohort of singleton pregnancies (n = 3,440), showed that longitudinal biometry calculated by linear mixed-effects models had lower sensitivities and did not provide additional information over cross-sectional measurement for predicting LGA (53 vs. 46% [p < 0.05] at ≤32 weeks). Nonetheless, as acknowledged by the authors, the main limitation of their study was that the number of scans varied among patients, making it difficult to rule out a selection bias whereby high-risk pregnancies are overrepresented.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that the differences in growth parameters between the sample restricted to women fulfilling the IG selection criteria and the overall population were very small is relevant for the current debate on growth standards vs. references. It shows that population selection is not an explanation for the differences between the IG standards and fetal growth in the ELFE cohort and is also unlikely to explain the differences found in other population‐based studies . More broadly, this finding challenges the relevance of distinguishing between growth “references” and “standards” for fetal growth monitoring, at least in high‐income settings where malnutrition is low and access to health services is high.…”
Section: Resultsmentioning
confidence: 83%
“…A comparison to the INTERGROWTH-21 st standard 16 was not performed due to differences in the ultrasound protocols that were previously noted 73 (eg the biparietal diameter was measured from the outer to the outer, while we measured from the outer to the inner, borders of the parietal bones) and also due to the different EFW formula used in the INTERGROWTH-21 st standard. Among the four standards compared in this study, there were significant differences in the fraction of fetuses classified as SGA (<10 th centile) based on the last available ultrasound examination for each pregnancy.…”
Section: Commentmentioning
confidence: 99%
“…However, comparing how the in utero SGA and LGA screenings based on different standards relate to an SGA or LGA diagnosis at birth and to adverse pregnancy outcomes was outside the scope of the current study. Of note, the ability of ultrasound-based estimated fetal weight to predict actual birthweight was described previously 14, 29, 73 . For example, in a blinded study conducted in a low-risk population, Sovio et al 29 reported that an EFW<10 th centile at 36 weeks of gestation correctly identified 57% of fetuses (sensitivity) that were destined to have a birthweight <10 th centile, with a specificity of 95%.…”
Section: Research and Clinical Implicationsmentioning
confidence: 99%